MOXIBUSTION ALLEVIATES GASTRIC PRECANCEROUS LESIONS IN RATS BY PROMOTING CELL APOPTOSIS AND INHIBITING PROLIFERATION-RELATED ONCOGENES - Peng, Li; Xie, Yu-feng; Wang, Chen-guang; Wu, Huan-gan; Liu, Mi; Wang, Ya-dong; Ma, Fu-qiang; Chang, Xiao-rong; Yang, Zong-bao (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: It is well known that gastric mucosa dysplasia and intestinal metaplasia are gastric precancerous lesions (GPL). Moxibustion treatment of Liangmen (ST21) and Zusanli (ST36) alleviated the inflammatory response and dysplasia of gastric mucosa in our previous study. The purpose of this study was to further examine the underlying mechanism of moxibustion treatment of ST21 and ST36 on GPL. Materials and Methods: Sixty SD rats were divided into five groups and rats with GPL were treated with either moxibustion (ST), moxibustion (Sham), or vitacoenzyme. B-cell lymphoma 2 (bcl-2), tumor protein p53 (P53) and cellular Myc (C-MYC), which are related to cell apoptosis, proliferating cell nuclear antigen (PCNA), vascular endothelial growth factor (VEGF), argyrophilic nucleolar organizer region proteins (Ag-NORs), which are associated with cell proliferation, and cell signaling proteins, nuclear factor kappa B (NF-κB), epidermal growth factor receptor (EGFR) and phosphorylated extracellular signal regulated kinase (p-ERK), were measured after moxibustion treatment. Results: Compared with Control group, gastric mucosa in GPL group showed abnormal mucosal proliferation and pathological mitotic figure, the mRNA expression of bcl-2, P53 and C-MYC increased significantly (P < 0.01), the protein expression of PCNA, VEGF, Ag-NORs and the activity of NF-κB as well as EGFR/ERK signaling proteins also increased significantly (P < 0.01). Moxibustion treatment decreased gastric mucosal proliferation and pathological mitotic figure, down-regulated the mRNA expression of bcl-2, P53, C-MYC (P < 0.01), decreased the protein expression of PCNA, VEGF, Ag-NORs and the activity of NF-κB as well as EGFR/ERK signaling proteins significantly (P < 0.01). But moxibustion treatment of Sham didn’t show the same effect on GPL. Conclusion: Moxibustion treatment inhibited cell apoptosis and reduced gastric mucosa dysplasia by inhibiting the expression of bcl-2, P53, C-MYC and decreased the activity of NF-κB as well as EGFR/ERK signaling proteins.